Implementasi Fatwa DSN-MUI NO.02/DSN-MUI/IV/2000 terhadap Akad Wadiah pada Produk Tabungan Easy Wadiah di Bank Syariah Indonesia - Risya Amanda Kusmana; Dzakwan Naufal Aziz; Muhamad Ibrahim; Estu Rahayu; Marsaadina Rizkillah Sa’diyyah; Asep Zakaria Anshori; Abdul Husenudin (Ikatan Da'i Indonesia, 2026)
The growth of Islamic banking in Indonesia reflects the public’s need for an alternative financial system based on Sharia principles. One concrete example of the implementation of the Islamic banking system is the existence of BSI (Bank Syariah Indonesia). Bank Syariah Indonesia (BSI) offers various savings products, including the Easy Wadiah Savings Account. The objective is to analyze the implementation of the Wadiah contract in the Easy Wadiah savings product at Bank Syariah Indonesia and to ensure the compliance of the Wadiah contract in the Easy Wadiah savings product with the DSN-MUI fatwa based on the DPS supervision report. This study employs a qualitative descriptive method to gain a comprehensive understanding of the implementation of the Easy Wadiah savings product at Bank Syariah Indonesia. Based on the research results, the implementation of the BSI Easy Wadiah Savings Account at Bank Syariah Indonesia (BSI) indicates that this product has been implemented in accordance with Islamic banking principles through the use of the Wadiah (deposit) contract, wherein Bank Syariah Indonesia acts as the party receiving and safeguarding customer funds in a trustworthy manner in accordance with Sharia provisions. Based on the official 2025 DPS report, all supervisory duties and responsibilities are assessed to have been carried out well and effectively in ensuring Sharia compliance across all lines of banking activity. The results of this study indicate that the application of the Wadiah contract in BSI Easy Wadiah Savings product is in accordance with Sharia principles as set forth in DSN-MUI Fatwa No. 02/DSN-MUI/IV/2000 on Savings.